Effects of Nudge Reflecting Day-of-Week Pattern against Induction to Walk - Mori, Takuya; Harada, Fumiko; Shimakawa, Hiromitsu (Advances in Social Sciences Research Journal, 2021)
This study proposes a tailored intervention method that takes individual contexts into account to increase walking steps in a sustainable way. Continuous exercise is necessary to reduce the risk of lifestyle-related diseases. However, many people are too busy to take constant exercises. Many existing approaches take enforcing ways in their support neglecting individual contexts, which prevents them to motivate individuals to exercise spontaneously. The proposed method figures out the periodicity of walking steps within every week. It regards the variation of the walking comes from inevitable contexts in the individual style of work and life. Reflecting the context, it encourages individuals with messages containing nudges. In a 4-week experiment with 13 university students, messages on days of the week of low walking succeeded in the improvement of the consciousness toward a healthy life. The use of periodicity and nudges turns out to be effective to lead individuals to sustained exercise.